(untitled) (UNWE Yearbook, 2015)
The paper presents the main ideas regarding the Great Depression of the prominent 20th century economists L. Robbins, W. Ropke and R. von Strigl. They write during the 1930s, and their theoretical views, although not identical, are developed within the framework of one paradigm. The author goal was to find oute those aspects in their works that would form a sound basis for better theoretical understanding of contemporary economic problems. The major and lasting conclusion that they reached is that, given the complexity of depression easy and simple solution to the problems it causes cannot be found.The authors considered made critical analysis of most conventional governmental measures to alleviate the Great Depression and to "liquidate" the business cycle. Their conclusion is that usually the results of these measures are radically different in comparison to the expectations. Thus the problem about the value and effectiveness of politically advantageous deeds of governmental “do-gooders” in the form of social and welfare policy, still could not be considered as finally solved.